Management of Malocclusion after Maxillofacial Trauma - Sharma, Ashish P.; Hondorp, Brian; Gaiduchik, Andrey; Baba, Nadim Z.; Thakker, Jayini; Inman, Jared C. (Facial Plastic Surgery, 2017)
Efficacious management of malocclusion following maxillofacial trauma requires understanding of the interaction between teeth and alveolar bone, facial skeleton, temporomandibular joints, and facial neuromusculature. Success is best achieved with a multidisciplinary approach. This article describes the management of malocclusion after primary repair by highlighting important clinical features and offering guidelines for secondary repair through revision surgical reduction, prosthodontic rehabilitation, orthodontic therapy, restorative dentistry, and orthognathic surgery.
Keywords: malocclusion; maxillofacial trauma; secondary repair; facial trauma; occlusion management